1995
DOI: 10.1073/pnas.92.16.7376
|View full text |Cite
|
Sign up to set email alerts
|

Cre-mediated site-specific translocation between nonhomologous mouse chromosomes.

Abstract: Chromosome rearrangements, such as large deletions, inversions, or translocations, mediate migration of large DNA segments within or between chromosomes, which can have major effects on cellular genetic control. A method for chromosome manipulation would be very useful for studying the consequences of large-scale DNA rearrangements in mammalian cells or animals. With the use of the Cre-loxP recombination system of bacteriophage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(77 citation statements)
references
References 20 publications
1
73
0
1
Order By: Relevance
“…However, PCR analysis of a pool of 200 clones did not show unambiguous evidence for the desired inter-chromosomal rearrangement (data not shown). This is in agreement with the ®ndings of other studies, which have reported translocation frequencies of less than 1 in 1000 (van Deursen et al, 1995;Smith et al, 1995). It is unclear at present, why the intrachromosomal rearrangement occurs at a much higher frequency than the inter-chromosomal event.…”
Section: *Correspondence: T Boehmsupporting
confidence: 92%
See 1 more Smart Citation
“…However, PCR analysis of a pool of 200 clones did not show unambiguous evidence for the desired inter-chromosomal rearrangement (data not shown). This is in agreement with the ®ndings of other studies, which have reported translocation frequencies of less than 1 in 1000 (van Deursen et al, 1995;Smith et al, 1995). It is unclear at present, why the intrachromosomal rearrangement occurs at a much higher frequency than the inter-chromosomal event.…”
Section: *Correspondence: T Boehmsupporting
confidence: 92%
“…A further signi®cant advantage of this strategy is that deletions can be generated in vivo. Previously, Cre-loxP recombination has been used to generate site-directed chromosomal translocations (Smith et al, 1995;van Deursen et al, 1995) and large deletions (Ramirez-Solis et al, 1995;Li et al, 1996). Our deletion strategy extends these ®ndings by incorporating the facility to recover intervening sequences in clonable form.…”
mentioning
confidence: 99%
“…De novo chromosomal translocations in mice using cre-loxP recombination An alternative approach to mimicing chromosomal translocations is the use of the Cre-loxP recombination system in ES cells to induce de novo chromosomal translocations (Smith et al, 1995;van Deursen et al, 1995). This has the advantage that tissue speci®c expression of the Cre recombinase would allow the translocation to occur in a tissue speci®c manner and, in addition, the de novo chromosomal translocation Figure 3 Lmo2 expression in vascularization of mouse embryos.…”
Section: An Mll-af9gene Fusion Knock-in Tumorigenesis Modelmentioning
confidence: 99%
“…The sequence-specific manipulation of DNA by Cre recombinase represents a powerful approach to studying gene function. Cre has been used to conditionally express, mutagenize, and replace genes (15)(16)(17)(18)(19)(20), as well as rearrange chromosomes (21)(22)(23)(24) in mice, resulting in major advances in the understanding of gene function. The requirement for preexisting genomic loxP sites complicates the use of Cre in studies of gene function and is an impediment to the use of Cre in applications such as gene therapy.…”
Section: Design Of Unnatural Loxp Sites and Cre Variant Librariesmentioning
confidence: 99%